Global well-posedness of the 3D magneto-micropolar equations with damping. (August 2019) - Liu, Hui; Sun, Chengfeng; Meng, Fanwei
Abstract: The 3D magneto-micropolar equations with damping are considered in this paper. We prove the existence and uniqueness of strong solution for 3D magneto-micropolar equations with damping for β ≥ 4 with any α > 0 .